15 N NUCLEAR MAGNETIC RESONANCE STUDY OF AMMONIUM ION ASSIMILATION BY LEMNA GIBBA L - Monselise, Edna Ben-Izhak (The New phytologist, 1987)
15 N Nuclear magnetic resonance (NMR) spectroscopy was used to follow nitrogen assimilation and amino acid production in Lemna gibba L. exposed to 0.4 mM 15 NH4 Cl solution for 24 h. NMR analysis of the 16 N content of the treated plant tissues (aqueous extract) revealed 15 N incorporation into glutamine (N-amide plus amino-N or amide-N only) and glutamic acid and no detectable free ammonium ion. Methionine sulphoximine (MSO), an inhibitor of glutamine synthetase, at 1.0 mM inhibited completely the incorporation of 15 N. In the presence of 0.5 mM azaserine (AZA), a glutamate synthase inhibitor, the incorporation of 15 N was detected only in the amide group of glutamine. The results confirm the involvement of the glutamine synthetase/glutamate synthase (GS/ GOG AT) pathway in the assimilation of ammonium ions